Prevalence of Helminthiasis in Cattle through Fecal Examination in Magetan Regency - Firda Shafa Salsabila; I Komang Wiarsa Sardjana; Suryanie Sarudji; Budiarto Budiarto; Poedji Hastutiek; Ririn Ririn (Universitas Airlangga, 2022)
This study aims to determine the prevalence of helminthiasis and find various kinds of egg worms in cattle through feces examination in Magetan Regency. A hundred cattle feces samples were collected from six animal markets in Magetan Regency. The Faecal examination was performed by native, sediments, and Flotation methods. The results of this study showed that there were 40 samples positively infected by a helminth, which indicated that the prevalence of helminthiasis in cattle was 40%. The kind of helminth were Oesophagostomum sp. (14%), Bunostomum sp. (8%), Mecistocirrus sp. (8%), Haemonchus sp. (4%), Toxocara vitulorum (3%), Trichuris sp. (2%), Strongyloides sp. (2%), and Fasciola sp. (11%).